The prevalence of soil transmitted helminth infections in minority indigenous populations of South-East Asia and the Western Pacific Region: A systematic review and meta-analysis - Gilmour, Beth; Alene, Kefyalew Addis; Clements, Archie C. A. (PLOS Neglected Tropical Diseases, 2021)
Author summary Neglected Tropical Diseases (NTD) are caused by a range of infectious pathogens and have their greatest impact on poor and vulnerable populations. One such population group, is indigenous people, who are disproportionately impacted by poverty and social disadvantage. Among the World Health Organization (WHO) list of 20 NTD, soil transmitted helminth (STH; Ascaris lumbricoides, Trichuris trichiura and hookworm) infections are the most prevalent and burdensome. This systematic review and meta-analysis evaluated the prevalence of STH infection in minority indigenous populations of the South-East Asia (SEAR) and Western Pacific Regions (WPR). The results showed a high prevalence of infection for all STH species in minority indigenous populations of both developing and highly industrialized nations. Of concern was the increasing prevalence of T. trichiura infection over time, which calls for the identification and implementation of more effective therapies and control strategies. Where comparative data were available, the review showed infection prevalence of all STH species not to be significantly different in minority indigenous people compared to those of other population groups. To help break the health burden and poverty cycle created by these infections, accurate, relevant data will be required to inform effective and appropriate interventions.